Chakras and energy alterations in patients with oligospermia - Huang Wei Ling (Archive of Urological Research - Peertechz Publications, 2020)
Introduction: Oligospermia is a male fertility problem characterized by a low sperm count. In Western Medicine, the causes of male sterility are mostly unknown. According to Traditional Chinese Medicine (TCM), oligospermia stems from Kidney deficiency.  Purpose: To demonstrate which are the chakras and energy alterations leading to oligospermia and how can we treat it.  Method: Two case reports. The first, C.X., a 29-year-old male, was diagnosed with non-obstructive oligospermia and second-degree left testicle varicocele. The seminal analysis found two spermatozoa per ml (6/4/2007). The TCM diagnosis was Yin/Qi Kidney Deficiency and Heat retention. The second patient named R, a 35-year-old male. He was trying to have a baby for three years without success. He was diagnosed with oligospermia (12 million per ml). The patient and his wife started treatment with Clomiphene, and after three months, the results showed less sperm than the first test (11 million per ml). A first IVF was done, with negative results. The couple searched for an energy-based treatment. He was diagnosed with Kidney Yin and Yang deficiency, Qi deficiency, Blood deficiency, and Heat retention. He received chakras measurement, with the use of radiesthesia. The result showed that on a scale from 1 to 8, the patient's chakras were measured in the level 1 (the minimum). Both patients were treated with Chinese dietary counseling, auricular acupuncture, and apex ear bloodletting. The second patient received crystal-based medication and homeopathy.  Results: In the first case, after three sessions, another Vitro fertilization procedure showed a surprising increase in spermatozoa (from 2 to 20 million per ml). His wife became pregnant after IVF procedure. The second patient couple was able to achieve a natural pregnancy within a month of treatment, not requiring the use of IVF. The woman was treated.  Conclusion: There are energy alterations and chakras energy deficiencies in patients with oligospermia and the treatment on the energy level are important to achieve good results.